Uganda : Technical Assistance Report-Implementing the Public Financial Management Bill. - International Monetary Fund. Fiscal Affairs Dept. (Washington, D.C. : International Monetary Fund, 2017)
This Technical Assistance Report discusses recommendations for implementing the Public Financial Management (PFM) Bill in Uganda. The finalization of the PFM Bill has reached an advanced stage with Parliamentary approval expected in the coming months. The IMF mission strongly recommends that the petroleum revenue management provisions in the Bill are revisited. In particular this should include clearly defining the nature of the funds and its objectives. The reporting arrangements should also be clarified and the specialist audit arrangements specified. Finally, the Bill should be enhanced to ensure that investment risks are limited and to protect against its use as a development fund.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet